2021
DOI: 10.5796/electrochemistry.20-00112
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Surface Analysis of LiMn<sub>2</sub>O<sub>4</sub> Thin-film Electrodes in LiPF<sub>6</sub>/Propylene Carbonate at Room and Elevated Temperatures

Abstract: Degradation of LiMn 2 O 4 in LiPF 6 -based electrolyte solution is complicated due to the influence of PF 6 − anion. Decomposition of PF 6− anion accelerates both of dissolution of manganese ion and surface-film formation. In this study, surface states of LiMn 2 O 4 thin-film electrodes in LiPF 6 /propylene carbonate (PC) derived from the surface-film formation were investigated using redox reaction of ferrocene and spectroscopic analyses. The spectroscopic analyses suggested that properties of the surface fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…This suggests that the reactions of acidic species generated from electrolyte oxidation on the cathode are more likely to cross over and damage the anode SEI than the dissolved transition metals. Since F 2 PO 2 H is also one of the species involved in the thermal autocatalytic decomposition of LiPF 6 in carbonates, this provides a good explanation for the significant difference in capacity retention upon a relatively small change in temperature (25 °C vs 45 °C). , Thus, developing electrolyte formulations or metal oxide surface films which inhibit the oxidation of LiPF 6 and EC to generate F 2 PO 2 H would lead to improve capacity retention in high voltage lithium ion batteries.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that the reactions of acidic species generated from electrolyte oxidation on the cathode are more likely to cross over and damage the anode SEI than the dissolved transition metals. Since F 2 PO 2 H is also one of the species involved in the thermal autocatalytic decomposition of LiPF 6 in carbonates, this provides a good explanation for the significant difference in capacity retention upon a relatively small change in temperature (25 °C vs 45 °C). , Thus, developing electrolyte formulations or metal oxide surface films which inhibit the oxidation of LiPF 6 and EC to generate F 2 PO 2 H would lead to improve capacity retention in high voltage lithium ion batteries.…”
mentioning
confidence: 99%
“…17,26 Thus, developing electrolyte formulations or metal oxide surface films which inhibit the oxidation of LiPF 6 and EC to generate F 2 PO 2 H would lead to improve capacity retention in high voltage lithium ion batteries. sı Supporting InformationThe Supporting Information is available free of charge at https://pubs.acs.org/doi/10.1021/acsenergylett.1c01657.…”
mentioning
confidence: 99%
“…It is well known that the serious capacity degradation of lithium batteries at high temperatures is a long-standing issue. High temperatures accelerate the occurrence of parasitic side reactions. Interestingly, the Li/CPE/LiFePO 4 battery at 55 °C presented improved capacity retention without detectable degradation over 100 cycles (Figure f) due to the high-temperature electrochemical stability of the obtained P­(EGDMA-EDT)-based electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…Thus far, we have investigated surface film formation behavior on various cathode materials. [15][16][17][18][19][20] As a result, we have found that the surface film was not always formed on cathode materials, and the formation behavior largely depended on the situation. For example, we have reported that the surface film formation behavior is greatly affected by the stability of lithium salt, temperature, and dissolution behaviors of transition metals.…”
mentioning
confidence: 93%